Sistem Pendukung Keputusan Pemilihan Mekanik Sepeda Motor Terbaik Menggunakan Metode Multi Objective Optimization on The Basis of Ratio Analysis (MOORA) - Alvita, Suha; Intan, Novia; Syahputra, Fajar; Ulfa, Kurnia; Ginting, Guidio Leonarde (STMIK Budi Darma, 2018)
In determining the best motorcycle mechanics, there are many criteria that must be owned by every mechanic as a condition to become a motorcycle mechanic best. Each of each company engaged in the sale or service of motorcycles has the criteria to determine who will be selected to become a motorcycle mechanic best. The selection of the best motorcycle mechanics is done to help improve the mechanical work to be better than the previous one. To assist in the determination or election in determining a person who is eligible to be the best motorcycle mechanic, a decision support system is required. In this research will be appointed a case that is looking for the best alternative based on criteria-Â¬ criteria that have been determined by using the method of Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA). The research is done by finding the weight value for each attribute, then done the ranking process that will determine the optimal alternative, that is the best motorcycle mechanic.